OP0039 Increased porosity in hand bones is strongly associated with distal radius fracture in elderly women. (23rd January 2014) - Dhainaut, A.; Hoff, M.; Syversen, U.; Haugeberg, G.
Abstract : Background: Distal radius fracture (fx) is one of the most common osteoporotic fx. Osteoporosis defined as T-score ≤-2.5 SD at spine and/or hip assessed by Dual Energy X-ray (DXA) has been identified as an independent risk factor for distal radius fx [1]. However, a large proportion of fragility distal radius fx occur in patients (∼68%) with T-score > -2.5 [2]. Assessment of bone structure e.g. cortical porosity may improve identification of individuals at high risk of fx [3]. Digital X-ray Radiogrammetry (DXR) used for quantitative measurement of metacarpal cortical hand bone mineral density (BMD) has been shown to predict distal radius fx [4]. This method also provides a quantitative measure of porosity. Objectives: To explore the association between increased cortical hand porosity assessed by DXR and risk of distal radius fx in elderly women. Methods: In this prospective case control study, women with distal radius fx (>50 years) were consecutively recruited from a community hospital. Age-matched controls were randomly identified in the national registry for the same catchment area and invited by mail. A hand radiograph from the non-dominant arm was used for DXR assessment and measurements included: BMD, porosity, cortical thickness and bone width. BMD at lumbar spine (L2-4) and femoral neck was measured by DXA. Statistical tests were applied using SPSS. Results: No significant difference was observed between the 114 distal radius fx patients and the 156 controls for age (67.7 vs 67.2 years, p=0.7), height (164.9 vs 163.8cm, p=0.1) or weight (68.9 vs 71.5 kg, p=0.1) nor for smoking, exercise, use of vitamin-D, bisphosphonates, estrogen or glucocorticoids. BMD was significantly reduced in fx patients compared with controls both in femoral neck (0.793 vs 0.838 g/cm 2, p=0.005) and spine (1.031 vs 1.099 g/cm 2, p=0.003) and for DXR hand (0.495 vs 0.522, p=0.003). For the individual components from which DXR BMD is calculated, a significant difference was seen for porosity (0.0124 vs 0.0109, p<0.001) and cortical thickness (0.149 vs 0.160, p=0.002), but not for bone width (0.822 vs 0.811, p=0.055). In univariate regression analysis, expressed as odds ratio (OR), a reduction in the following variables were found to be significantly associated with a distal radius fx: DXR BMD (OR 1.005 per mg, p=0.004), DXA BMD (femoral neck OR 1.003 per mg, p=0.006, spine OR 1.002 per mg, p=0.004) and cortical thickness (OR 1.013 per mm, p=0.002), whereas an increase in porosity was found to be associated with an increased risk of distal radius fx (OR 7.3 per % point increase, p<0.000). In a multivariate regression model including variables with p<0.2 in the univariate analysis, (DXR BMD and cortical thickness exluded due to linearity) porosity remained significantly associated with distal radius fx (OR 10.08 per % point increase, p=0.001). Conclusions: Our results suggest cortical bone porosity, a measure of bone structure, to play a major role in increasing distal fracture risk in elderly women. References: Oyen et al. Osteoporosis Int 2010 Oyen et al. Osteoporosis Int 2009 Zebaze et al. Lancet 2010 Bouxein et al. Osteoporosis Int 2002 Disclosure of Interest: None Declared